Free choice in the making: Vaccine-related activism as an alternative form of citizenship during the Covid-19 pandemic. - Morsello, Barbara; Giardullo, Paolo (PARTECIPAZIONE E CONFLITTO, 2023)
The paper analyzes how free vax communities reframe health emergency during Covid-19 pandemic. We examined, through a digital ethnography on the main Italian free-vax online communities - Comilva, Corvelva and Movimento 3V – the public contestation of anti-Covid health policies by comparing their different styles of vaccine-related activism. Contesting health policy during pandemic was not just a matter of misinformation or related to the spreading of fake news, but actions and claims of free vax communities were based on specific processes of knowledge-making and biopolitics. The Science and Technology Studies (STS) framework, adopted throughout the analysis, provides the opportunity to review the vaccination controversies debate, by focusing on free vax public activities, aimed at counteracting mainstream knowledge and health policies adopted by the government to face the Covid-19 emergency. The analysis offers an entry point for understanding the nexus among the claims of free vax communities and the emerging idea of citizenship related to health, individual rights, and public participation in contemporary society.